Quality of Cotesia flavipes (Hymenoptera: Braconidae) reared at different host densities and the estimated cost of its commercial production - Vacari, Alessandra M. [UNESP]; De Bortoli, Sergio A. [UNESP]; Borba, Dionisio F. [UNESP]; Martins, Maria I. E. G. [UNESP] (Academic Press Inc. Elsevier B.V., 2012)
The objective of this study was to evaluate the quality of the parasitoid Cotesia flavipes (Cameron) reared at different densities of its host, Diatraea saccharalis (Fabr.), and to estimate the costs of its production. After parasitism, we placed hosts in petri dishes at densities of three, four or five larvae per dish and evaluated the biological characteristics of the parasitoids throughout their lifespan. We measured the body length, body width, abdomen width, thorax width, and width and length of the right forewing of female and male parasitoids. We discovered that host density affected the parasitoid sex ratio. The different host densities per dish resulted in a similar lifespan. A host density of three larvae per dish resulted in a better sex ratio. Parasitoids reared at different host densities per dish had similar body lengths. Therefore, a density of 5 D. saccharalis larvae per dish is suitable for mass rearing of C. flavipes. At this host density, the cost associated with rearing C. flavipes is USD 0.05 per pupal mass. Crown Copyright (C) 2012 Published by Elsevier B.V. All rights reserved.
Keywords: Mass rearing; Biological control; Sugarcane